2014
DOI: 10.1039/c3dt53012d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of heteroboroxines with MB2O3 core (M = Sb, Bi, Sn)—an influence of the substitution of parent boronic acids

Abstract: The synthesis and structure of stiba-, stanna- and bismaheteroboroxines of a general formula L(E)M[(OBR)2O] supported by a N,C,N-chelating ligand L [where L = C6H3-2,6-(CH2NMe2)2, M, E = Sb, lone pair or Sn, Ph or Bi, lone pair] is reported. The target compounds are prepared by straightforward one-step reactions between oxides (LMO)2 (M = Sb or Bi) or organotin(iv) carbonate L(Ph)Sn(CO3) with four or two molar equivalents of corresponding organoboronic acid. All compounds were characterized with the help of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 90 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Boroxines are rigid bidentate ligands which have drawn attention recently, mostly by forming complexes of main group elements, e.g. for Al; [38][39][40] Sn, Sb and Bi; [41][42][43][44][45][46][47] but also for transition metals such as Mn, 48 Au 37,49 and Pt. 50 Single crystals of 5 m and 6 m were obtained by slow diffusion of hexanes into a benzene solution.…”
Section: Triphenylphosphine Oxidementioning
confidence: 99%
“…Boroxines are rigid bidentate ligands which have drawn attention recently, mostly by forming complexes of main group elements, e.g. for Al; [38][39][40] Sn, Sb and Bi; [41][42][43][44][45][46][47] but also for transition metals such as Mn, 48 Au 37,49 and Pt. 50 Single crystals of 5 m and 6 m were obtained by slow diffusion of hexanes into a benzene solution.…”
Section: Triphenylphosphine Oxidementioning
confidence: 99%
“…Recently, the donor–acceptor N→B bonds were successfully used for the construction of macrocycles, cagelike compounds, or one-dimensional (1D), two-dimensional (2D), or 3D networks. However, a clear majority of these adducts is based on boronic esters or boroxine rings, and only a handful of compounds with B–O–Z (Z ≠ B, C, H) moiety were reported containing N→B bonds. These are (N,O-κ 2 -H 2 N­(CH 2 ) 3 O)­(RO)­B­(μ-O)­SiPh n Me 3– n (R = Ph, n = 0, 1, 2, 3; R = t Bu, n = 1, 2, 3), , [ t BuSi­{O­(PhB)­O} 3 Si t Bu] n ·L (L = pyridine, n = 1; L = Me 2 NCH 2 CH 2 NMe 2 , n = 2), and {2,6-(CH 2 NMe 2 ) 2 -C 6 H 3 }­Sn­(OBPy) 2 (μ-O) (py = pyridine) . Therefore, we became interested in the coordination of boron atoms in the borosilicate rings with an organic diamine.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of organotin­(IV) carbonate (L- k 3 N 2 C )­PhSnCO 3 ( 1 ) with organoboric acids RB­(OH) 2 at a 1:2 molar ratio provided the corresponding organotin­(IV) stannaboroxines (L- k 3 N 2 C )­PhSn­(O 3 B 2 R 2 ), where L = [2,6-(Me 2 NCH 2 )­C 6 H 3 ] − and R = Ph ( 2 ), 4-Br-Ph ( 3 ), 3,5-(CF 3 ) 2 -Ph ( 4 ), and 4-CHO-Ph ( 5 ) (Scheme ). Compounds 2 , 3 , and 5 were prepared and characterized according to the literature . Compound 4 was characterized by NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was demonstrated that the boron atom of the boroxine ring can be easily substituted by metal atoms to give a variety of metallaboroxines of the general formula M­(O 3 B 2 R 2 ), where M is Pt, Al, Sb, Bi, or Sn . Later on, we have provided the easy preparation of new stannaboroxines of the general formula (L- k 3 N 2 C )­PhSn­(O 3 B 2 R 2 ), where L is 2,6-bis­(dimethylaminomethy)­phenyl and R is an aryl substituent, respectively, containing a six-membered SnB 2 O 3 ring . Our extensive research in the field of stannaboroxine systems has also provided the synthesis of a new type of stannaoxidoborate, H­[(L- k 2 NC )­SnB 4 O 6 R 4 ], derivatives of the pentaborates [B 5 O 6 R 4 ] − in which the central boron atom is substituted by a tin atom.…”
Section: Introductionmentioning
confidence: 99%